Galang Bhakti Sosial Camp Strengthens Role of Nahdlatul Ulama Youth In The Community - Safitri, Eka; Sustriawan, Budi; Sa'dudin, Ihsan (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2023)
This research is one of many efforts to deliver this program Kemah Galang Bhakti Sosial (KGBS) is a program that can expand the role of youth NU in the Ayah sub-district, Kebumen district. As for the method of writing, this research is a descriptive analysis method for scrutinizing true conditions, and the results of this research are analyzed and shown in a report of research. The result of this research is the KGBS program, which has become a place for youth NU to advance NU. Besides that, this program can be a realization of the contribution of youth NU in the Ayah subdistrict in education, politics, social, religion, and culture areas.